Characterization of Patients with Guillain-Barré Syndrome in the General Hospital of Mexicali - Fátima María Martínez-González; Jeremy Hernández-Ríos; Arely Gutiérrez; Andrés Beltrán; René González; Hiram Jaramillo-Ramírez (University Library System, University of Pittsburgh, 2019)
Background: Guillain-Barré Syndrome is a progressive autoimmune polyradiculoneuropathy characterized by symmetrical flaccid paralysis accompanied by areflexia, hyporeflexia or hyperreflexia on rare occasions. Worldwide, it remains the first cause of flaccid paralysis. It is usually associated with infectious disease history; however, there are various clinical variants, each with a different outcome. Prognosis is usually good, although 20% of patients could suffer a severe clinical variant of Guillain-Barré Syndrome and 5% will die despite treatment. Methods: This is a cross-sectional study, including the records of hospitalized patients with Guillain- Barré Syndrome at Mexicali's General Hospital within a five-year period. Results: In a five-year span there were 64 patients with Guillain-Barré Syndrome, most of the patients were men (70.3%), with age ranging 1 to 76 years. A total of 8 (12.5%) patients died, from which 7 (87.5%) required mechanical ventilation during hospitalization. Immunoglobulin therapy was provided to 56 (87.5%) patients, and 6 (10.7%) of them perished due to acute kidney injury. Conclusion: Guillain-Barré Syndrome is a common disease among male population, with no dominating onset age, however, leaning for the young and elder. Most of the patients that were hospitalized at the General Hospital of Mexicali had a history of previous infection (gastrointestinal, respiratory, or other infectious diseases). The need for mechanical ventilation represents a higher severity index, nonetheless, this does not mean that assisted ventilation is directly associated with mortality. As for treatment, immunoglobulin is the most common choice for therapy, though some of the patients died from acute kidney injury.